Bank Loan Loss Provisions Behaviour: An Empirical Analysis of Hong Kong’s Banking Industry 2006-2012 - Kwok, Ka Po (2014)
This paper investigates loan loss provisioning behaviour in Hong Kong’s banking industry from 2006 to 2012, covering pre and post global financial crisis periods, to identify the changes in the banking system. It considers the business cycle, income smoothing, risk management, control variables of size and market concentration and examines whether including X-efficiency affects loan loss provision behaviour. It is found that there is pro-cyclical behaviour in loan loss provision, and this is a reflection of risk-based regulations adopted in Hong Kong. The study reveals that the root causes of changes in loan loss provision is regulations and therefore all the risk management measures are insignificant to loan loss provisions. The study also clearly identifies the positive impact of X-efficiency on loan loss provision.